Analysis of the effectiveness of individualized treatment regimens for nontuberculous mycobacterioses - Shevchenko, O; Kalmykova, I; Novohatska, M; Shyrapova, O; Pogorelova, O (Annals of Mechnikov’s Institute, 2019)
Despite the fact that in Ukraine, as well as worldwide the incidence of nontuberculous mycobacterioses is growing, in our country there are still no standardized protocols for their diagnosis and treatment, which makes it impossible to prescribe adequate chemotherapy and worsens the prognosis of treatment. We have retrospectively studied medical histories of 26 patients who were diagnosed with "pulmonary non-tuberculous mycobacteriosis" during 2014-2016. The diagnosis of "non-tuberculous mycobacteriosis" was established based on the growth of non-tuberculous mycobacteria (NTMB) in BACTEC system, and then verified by the absence of Cord-factor formation, negative immunochromatographic test, negative GeneXpert MTB / RIF. Based on the results of the studies, it was determined that 17 patients had slow-growing chromogenic NTMB and 9 patients had slow-growing non-chromogenic NTMB. With the use of 2HRZE regimen, 83.3% of patients with slow-growing chromogenic NTMB underwent laboratory recovery, and only 41.7% of patients had clinical and X-ray recovery. However, patients who received the individual regimen (2R(Rfb)Z(E)LfxKm) had a rapid positive dynamics, clinical, radiological and laboratory recovery until the end of intensive phase. In patients with slow-growing non-chromogenic NTMB, all three regimens (2HRZE, 2R(Rfb)Z(E)LfxKm, 2R(Rfb)Z(E)LfxClr) proved to be effective. We believe that it is necessary to improve level of identification of NTMB for the timely appointment of an adequate chemotherapy regimen.